Improving the fire performance and smoke suppression of expandable polystyrene foams by coating with multi‐dimensional carbon nanoparticles. Issue 40 (17th March 2020) - Cao, Bo; Yu, Ting; Sun, Jun; Gu, Xiaoyu; Liu, Xiaodong; Li, Hongfei; Fei, Bin; Zhang, Sheng
Abstract: Expandable graphite (EG) and modified multi‐wall carbon nanotubes (ATH‐MWNT) were introduced to expandable polystyrene (EPS) foams in order to improve its fire performance. The fire performance of EPS foams was evaluated by limiting the oxygen index (LOI), vertical burning (UL‐94), and cone calorimetry tests. The results showed that the presence of 14.3% EG and 4.1% ATH‐MWNT increased the LOI value from 18.0 to 30.3%, upgraded the UL‐94 rating from no rating to V‐0, completely eliminated melt dripping, and significantly decreased the peak heat release rate from 933 to 177 kW/m 2 . Thermal analysis indicated that the thermal stability and char formation were improved by the presence of flame retardants. The char morphology was characterized by scanning electronic microscopy (SEM). It was suggested that the presence of EG and ATH‐MWNT could form integrated char layers during combustion, which was beneficial to the formation of an intumescent protective char structure. Abstract :